The Almost Forgotten Library: Revisiting Toxic Sources - Merican, Ahmad Murad Mohd Noor; Mohamad, Radia Banu Jan; Jan, Noor Azlinda Wan; Fesal, Fujica Azura (2017)
The modern library is an almost forgotten species. With the Internet, new technologies and social media, the library has changed to being an information resource repository of the world. The World Wide Web has thus become the library. But what does that mean? How does that factor in universal versus local knowledge? How does that facilitate us in terms of domination and empowerment? This paper looks at the need for revisiting the library and a sense of reconciliation with the past by non-Western societies. If the whole world is the library, which world are we or should we be most concerned with.